Exploratory Impact of iCARE Nigeria, a Combined mHealth and Peer Navigation Intervention, on Depressive Symptoms and Substance Use Among Youth Living With HIV in Nigeria: Single-Arm Trial - Olusegun Ayomikun Ogunmola; Rita Frinue Tamambang; Kehinde Kuti; Lisa M Kuhns; Olutosin Awolude; Adedotun Adetunji; Bibilola Oladeji; Oladayo Olaleye; Adeola Mary Oyerinde; Robert Garofalo; Babafemi Taiwo; Olayinka Olusola Omigbodun (JMIR Formative Research)
Abstract BackgroundMental health problems are a barrier to the well-being of youth living with HIV. Many youth living with HIV in Nigeria face peculiar biopsychosocial vulnerabilities that predispose them to mental health problems including depression and substance use. In addition to improving treatment outcomes like medication adherence and linkage to care, peer engagement has shown some promise in improving the social and emotional well-being of this population. Mobile health (mHealth) interventions like SMS text messaging medication reminders may also contribute to better outcomes in youth living with HIV. Emerging evidence suggests that combination interventions may be more effective than single interventions in improving key HIV testing and treatment outcomes among youth in Nigeria. ObjectiveThis study aims to explore the impact of Intensive Combination Approach to Rollback the Epidemic in Nigerian Adolescents (iCARE Nigeria) study—an mHealth and peer navigation intervention primarily aimed at medication adherence and viral suppression—on depressive symptoms and substance use among youth living with HIV in Nigeria. MethodsA single-arm clinical trial was conducted at the Infectious Disease Institute, College of Medicine, University of Ibadan, Nigeria— primarily to improve medication adherence and viral suppression among youth living with HIV attending its HIV clinic. The intervention combined peer navigation and daily, 2-way, text message medication reminders delivered over a period of 48 weeks. Participants were screened at baseline and follow-up visits (24 and 48 weeks) for depression and substance use using standardized measures. Paired t ResultsAll 40 enrolled participants (n=20, 50% male; mean age 19.9 y, SD 2.5 y) completed baseline and follow-up visits at week 24, while 37 (92.5%) participants completed the week 48 visit. Compared with baseline, there were significantly fewer self-reported depressive symptoms observed at 48 weeks (mean 2.89 vs 2.08; t36t36 ConclusionsThese findings suggest a statistically significant reduction in depressive symptoms among youth living with HIV over the 48-week intervention period that may be due to the iCARE Nigeria intervention. However, given limitations such as low levels of depressive symptoms at baseline, small sample size, and the lack of a control group, future studies such as the randomized stepped wedge evaluation of the iCARE intervention are needed to provide better insights into these exploratory findings.